Kepemimpinan Organisasi Pendidikan - Dedi Eko Riyadi HS (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2022)
It has become a common understanding that leadership is a process of influencing other people (subordinates or other people) with some special skills possessed, all of which lead to achieving organizational or group goals. The leadership of an educational organization is the ability to influence, coordinate, guide, and try as much as possible to mobilize other people, especially their subordinates or those they lead with one goal, namely the development of educational science and the implementation of education and teaching. All this is done so that the activities carried out in this educational organization run in accordance with the expectations that have been formulated together, namely being efficient and effective in achieving the goals of education and teaching. Telah menjadi pemahaman bersama bahwa kepmemimpinan adalah proses mempengaruhi orang lain (bawahan atau orang lain) dengan beberapa keahlian khususu yang dimiliki yang kesemuanya itu bermuara yaitu untuk mencapai tujuan organisasi atau kelompok. Adapaun kepemimpinan organisasi pendidikan adalah suatu kemampuan mempengaruhi, mengkoordinir, membimbing, dan berusaha semaksimal munkin mengeerakkan orang lain terutama bawahannya atau yang dipimpinnya dengn satu tujuan yaitu pengembangan ilmu pendidikan serta pelaksanaan pendidikan dan pengajaran. Semua ini dilakukan agar kagiatan yang dilakukan dalam organisasi pendidikan ini berjalan sesuai dengan harrapan yang telah dirumuskan bersama yaitu efisien dan efektif dalam mencapai tujuan tujuan pendidikan dan pengajaran.